2022
DOI: 10.1002/jso.26823
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative C‐reactive protein to prealbumin ratio is independently associated with prognosis in patients with resectable colorectal cancer

Abstract: Background: Increasing attention has been drawn the prognostic value of inflammatory indices for colorectal cancer (CRC). However, the prognostic value of the preoperative C-reactive protein to prealbumin ratio (CPAR) in CRC remains unclear. Methods: A retrospective study was conducted with 794 patients who had CRC and underwent radical surgical resection. The predictive performance of the inflammatory indices was analyzed and compared using the area under the timedependent receiver operating characteristic cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…We have read with interest the article published by Huang et al 1 Although we believe it is a very interesting topic, we would like to offer the following points for your consideration.…”
Section: Preoperative C-reactive Protein To Prealbumin Ratio Is Indep...mentioning
confidence: 99%
“…We have read with interest the article published by Huang et al 1 Although we believe it is a very interesting topic, we would like to offer the following points for your consideration.…”
Section: Preoperative C-reactive Protein To Prealbumin Ratio Is Indep...mentioning
confidence: 99%
“…The Cox model also ignores the mutually exclusive relationship between target and competing events, leading to the overestimation of true observations. The competing risk model is suitable for the processing of event data and can obtain approximately unbiased results that are close to the truth ( 18 ). The choice of survival analysis method is critical in the nomogram construction process.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the CRP to prealbumin ratio (CPAR), which is an inflammatory and nutritional marker, has been investigated as a potential prognostic indicator in various cancers [ 6 , 8 ]. In this issue of the Korean Journal of Clinical Oncology , Kwon et al [ 9 ] demonstrated the utility of CPAR in predicting the prognosis of PDAC.…”
mentioning
confidence: 99%
“…breast cancer [3,[5][6][7]. Furthermore, prealbumin has a shorter halflife which is about 2 to 3 days, and is considered more sensitive and accurate biomarker than albumin.…”
mentioning
confidence: 99%